Ona Randall honored at tea (Raton Range Raton, New Mexico, 1984)
Newspaper Article on the 90th birthday of Ona Randall.
Master list item #: 44
File location is in the Raton File Cabinet
Keywords: Randall, Ona; Randall, Greg; Sims, Jesse; Butt, Della Mae; Woodward, Betty; Trantham, Anna; Stilinovich, Pauline; Smith, Bennie; First United Methodist Church; Local History; Biogrpahy; Life and Customs; Birthday; Celebration; Raton, New Mexico; Las Cruces, New Mexico